EDUKASI ISI PIRINGKU DENGAN METODE PENDEKATAN PEMBUATAN SALAD BUAH SEGAR DI SMP YARI PADANG - Nadia Purnama Dewi; Zuhrah Taufiqa; Ade Teti Vani; Irwan Triansyah; Dessy Abdullah; Aryaldi Zulkarnaini (Yayasan Nusantara Hasana Berdikari, 2024)
Motivation/Background: Good nutritional knowledge is crucial for teenagers to support optimal growth and development. Comprehensive nutrition education is very important for teenagers to understand the importance of a balanced diet, according to the